2021
DOI: 10.21203/rs.3.rs-203015/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Particle Swarm Optimization Based Multi-Objective User Association for LTE-A Heterogeneous Networks

Abstract: Heterogeneous networks (HetNets) are a promising communication paradigm to satisfy the diverse requirements of Long Term Evolution-Advanced (LTE-A). Associating users with different base station tiers using the conventional technique based on the highest received SINR is not viable in HetNets due to its rigid association, which only aims at throughput maximization. Many e orts have been made to tackle the optimization problem of user association with a single objective such as throughput, fairness or energy ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The updating expressions of LSTM are described in Equations ( 16) to (20). W Fy , W By signifies the weight of forward and backward LSTM.…”
Section: Deep Bidirectional Battle Royale Long Short Term Memory (Dee...mentioning
confidence: 99%
See 2 more Smart Citations
“…The updating expressions of LSTM are described in Equations ( 16) to (20). W Fy , W By signifies the weight of forward and backward LSTM.…”
Section: Deep Bidirectional Battle Royale Long Short Term Memory (Dee...mentioning
confidence: 99%
“…Both base stations are highly independent with two dimensional Poisson point process (PPPs) to imprison the irregular network structure. Summakieh et al 20 suggested particle swarm optimization using multiobjective in LTE-HetNet. The suggested multi objective user technique had enhanced the network throughput and network balance index (NBI).…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation